KONSEP “KHALÎFAH FÎ AL-ARD” DALAM PERSPEKTIF ETIKA LINGKUNGAN - Atikawati, Dini; Gunawan, Totok; Sunarto, Sunarto (Bumi Lestari, 2019)
Various environmental problems occur due to human behavior. This behavior is influenced by the way a person views his environment. The perspective is influenced by the values ??believed. Inappropriate behavior and low morale in managing the environment will cause damage. For this reason, a concept of human leadership is needed for nature which can be used as a guide for environmental management. This article aims to examine the concept of khalîfah fî al-ard in environmental ethics perspective. This article is the result of an in-depth study of relevant libraries. This article argues that the concept of khalîfah fî al-ard   originating from the Qur'an is very relevant to environmental ethics biosentrism and ecocentrism. The concept of khalîfah fî al-ard which is interpreted as the representative of Allah on earth should be a human starting point in managing and maintaining the environment, so that this concept is one of the strategic means of structuring and maintaining the environment. The concept of khalîfah fî al-ard can be realized into a pro-environment movement. It is very important for us as Muslims to understand the essential meaning of ourselves as khalîfah fî al-ard who cares the earth from damage.